IMPLEMENTATION OF INQUIRY METHOD IN LEARNING ISLAMIC CULTURAL HISTORY (SKI) TO IMPROVE STUDENT LEARNING OUTCOMES - Agustina, Ike Yama; Nurdiansyah, Yohan Viko (Sekolah Tinggi Ilmu Tarbiyah (STIT) Al-Ishlah Bondowoso, 2023)
Education is the conscious guidance of educators towards the physical and spiritual development of students towards the formation of humans who have an ideal personality. Therefore, teachers as educators must be able to carry out new models of education with educational procedures that are suitable for student participants. One of the educational strategies recommended in the 2013 curriculum is the Inquiry Strategy. The inquiry learning strategy is a form of a learner-oriented learning approach (student centered approach.). A person is said to be successful or not in the learning process due to a factor, namely the first comes from the student as a learner (internal) and the second comes from outside the student (external). Learning the history of Islamic culture contains good values that can be utilized for careful training in shaping students' attitudes and personalities. The use of this research writing approach is a qualitative approach. This is because the implementation of actions to the research subject is prioritized to explain how the teaching and learning process and how efforts to improve student learning outcomes. The application of methods that are carried out repeatedly makes students experience a very significant increase in learning outcomes because students are getting used to the inquiry method.